Pergeseran Perilaku Pedagang Pasar Legi Kabupaten Ponorogo Pasca Revitalisasi Ditinjau Dari Sosiologi Ekonomi Islam - Bilkys Cantika Kavarera; Aji Damanuri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Ponorogo Legi Market, the largest traditional market and main trading hub in Ponorogo Regency, which faces challenges due to its poor physical condition and inadequate management. The research aims to identify factors influencing trader behavior shifts and the impact of market revitalization on these behaviors, using an Islamic economic sociology framework. Employing a qualitative approach, data were collected through observation, interviews, and documentation. Findings reveal that trader behavior is shaped by internal factors (motivation, experience, personality) and external factors (competitor threats, government regulations, socio-economics). The revitalization has yielded mixed outcomes: it fosters a sense of community among traders (Shilat al-Rahim) but also leads to economic and management challenges, such as reduced income and rule violations.